PENGARUH WORD OF MOUTH, DAYA TARIK WISATA DAN HARGA TERHADAP KEPUTUSAN BERKUNJUNG (Studi Kasus Pada Pengunjung Waterboom 88 Bululawang) - Gusti Wahyuning Vilda; M. Hufron; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the effect and analyze word of mouth, tourist attraction and price simultaneously and partially on visiting decisions. The population in this research are visitors at Waterboom 88 Bululawang. The sample was taken using the Slovin formula in order to obtain 97 respondents who met the requirements as the sample. This research was conducted by providing a questionnaire and using multiple linear regression analysis method. The results of this study indicate that: (1) the variable word of mouth, tourist attraction and price simultaneously influence the decision to visit Waterboom 88 Bululawang. (2) the variable word of mouth has a positive and significant effect on the decision to visit Waterboom 88 Bululawang. (3) the tourist attraction variable has a positive and significant effect on the decision to visit Waterboom 88 Bululawang. (4) the price variable has a positive and significant effect on the decision to visit Waterboom 88 Bululawang.  Keyword: Word Of Mouth, Tourist Attraction, Price, Visit Decesion